An Ethnozoology of Malay Tribe in Bagan Serdang Village, Pantai Labu District - nasution, aswarina; Dyah Puspitasari2, Wina; Ratna Anjaning Kusuma, Dwi; Shafwan S. Pulungan, Ahmad (Universitas Negeri Medan, 2026)
Bagan Serdang Village is one of the villages in the Pantai Labu District, Deli Serdang Regency, North Sumatra Province. This coastal area boasts abundant natural resources, including seafood, tourism, agriculture, and fisheries. The aim of this research is to uncover, analyze and synthesize the believe (cosmos) and local knowledge (corpus) of the Malay community in Bagan Serdang Village in processing and utilizing (praxis) animal around the coast. This type of research is an exploratory survey with an emic and etic approach. The research sources are key informants selected through purposive sampling techniques. Data collection through interviews, observations, and species inventories. Data analysis was carried out by qualtative type (reduction, display and verification). The results of the study showed that there are 28 animal species were found to be used for various purposes, ranging from food sources, medicine, and rituals. Some of these animal are processed before use, but many are also unprocessed.